Modeling low energy x-ray interactions with biological material at the CUEBIT. (29th January 2015) - Klingenberger, J; Schott, M; Kimmel, T; Medlin, D; Gall, A; Rusin, M; Dean, D; Takacs, E
Abstract: Recent developments at Clemson University have established the need to model the production of x-rays using a highly charged ion beam generated by the Clemson University Electron Beam Ion Trap (CUEBIT). A Geant4 modeling environment has been developed on Clemson University's Palmetto2 supercomputing cluster to simulate the interaction of these x- rays with biological material. Preliminary results of the model have been obtained after performing initial simulations on the computing cluster. Future experiments using the CUEBIT as well as refinements to the Geant4 model are discussed.